The impact of public health interventions on critical illness in the pediatric emergency department during the SARS‐CoV‐2 pandemic. Issue 6 (10th August 2020) - Dean, Preston; Zhang, Yin; Frey, Mary; Shah, Ashish; Edmunds, Katherine; Boyd, Stephanie; Schwartz, Hamilton; Frey, Theresa; Stalets, Erika; Schaffzin, Joshua; Vukovic, Adam A.; Reeves, Scott; et al.
Abstract: Study objective: The impact of public health interventions during the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic on critical illness in children has not been studied. We seek to determine the impact of SARS‐CoV‐2 related public health interventions on emergency healthcare utilization and frequency of critical illness in children. Methods: This was an interrupted time series analysis conducted at a single tertiary pediatric emergency department (PED). All patients evaluated by a provider from December 31 through May 14 of 6 consecutive years (2015‐2020) were included. Total patient visits (ED and urgent care), shock trauma suite (STS) volume, and measures of critical illness were compared between the SARS‐CoV‐2 period (December 31, 2019 to May 14, 2020) and the same period for the previous 5 years combined. A segmented regression model was used to explore differences in the 3 outcomes between the study and control period. Results: Total visits, STS volume, and volume of critical illness were all significantly lower during the SARS‐CoV‐2 period. During the height of public health interventions, per day there were 151 fewer total visits and 7 fewer patients evaluated in the STS. The odds of having a 24‐hour period without a single critical patient were >5 times higher. Trends appeared to start before the statewide shelter‐in‐place order and lasted for at least 8 weeks. Conclusions: In a metropolitan area without significant SARS‐CoV‐2 seeding, the pandemic was associated with a marked reduction in PED visits for critical pediatric illness.